A simulated trading platform in a classroom - Sun, Qiyang (Nanyang Technological University, 2024)
This project entails the development of a web-based trading simulation platform designed to transition manual, pen-and-paper trading exercises into a digital, seamless, and efficient format. Within this educational context, students will engage in simulated trading activities, making decisions based on historical stock prices.